2017
DOI: 10.1159/000465529
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients, Essential Fatty Acids and Bone Health in Phenylketonuria

Abstract: Introduction: In phenylketonuria (PKU), a natural protein-restricted dietary treatment prevents severe cognitive impairment. Nutrient deficiencies may occur due to strict diet. This study is aimed at evaluating the dietary intake and blood concentrations of micronutrients and essential fatty acids (FA), bone mineral density (BMD) and fracture history in patients on long-term dietary treatment. Methods: Sixty early diagnosed Dutch patients (aged 1-39 years) were included in a multi-center cross-sectional study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 47 publications
2
31
2
Order By: Relevance
“…Importantly, this is comparable to the percentage reported by us [1], even though they describe a population with mainly adult patients.…”
Section: Dear Editorssupporting
confidence: 88%
See 2 more Smart Citations
“…Importantly, this is comparable to the percentage reported by us [1], even though they describe a population with mainly adult patients.…”
Section: Dear Editorssupporting
confidence: 88%
“…Approximately 4.9-7.4% of early treated patients with PKU may have a BMD Z-score below -2 SD, as opposed to 2.5% in the general population. This means that approximately 95% of early treated Dutch patients with PKU are not at risk for low BMD, and this is a much better outcome than expected from reports in the literature [1,6].…”
Section: Dear Editorsmentioning
confidence: 82%
See 1 more Smart Citation
“…Demirdas et al [1] have reported that 42% of 60 phenylketonuria (PKU) patients (median age 13 years, 58% female) sustained ≥1 fracture and have described bone mineral density (BMD) in a subset. These authors have concluded that "low BMD (Zscore <-2) was slightly more prevalent in patients" and "the lifetime fracture prevalence of patients seems comparable to the general population (41.7 vs.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Unfortunately, several points need clarification. We hereby recommend that Demidras et al [1] reanalyze their data in the following manner:…”
Section: Dear Editorsmentioning
confidence: 99%